2020
DOI: 10.3390/nano10040622
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Synthesis Using Stainless Steel as Solid Reductant: A Critical Overview

Abstract: Gold nanoparticles (AuNPs) were produced using stainless steel as a solid reductant to assist the synthesis of metal NPs, using HAuCl4 as a precursor. This method is very easy, quick, and cost-effective, allowing the synthesis of highly stable NPs without additional capping agents. However, the reaction mechanism is still under debate. In order to contribute to the investigation of the synthesis of AuNPs using stainless steel, different experimental conditions were tested. Cl− concentration, pH of the precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…[60] To this extent, many nanomaterials, both carbon-based nanomaterials (e.g., multiwalled carbon nanotubes, [61][62][63] reduced graphene, etc.) and metal/metal oxide-based nanoparticles [64][65][66] have been used to develop external gate electrodes that exhibited a pH sensitivity by means of potentiometric measurements. [67][68][69] In this regard, Yin et al reported on the development of an H + ion-sensitive EG-FET by using an indium tin oxide (ITO) electrode modified with tin oxide (SnO 2 ) by a sputtering method.…”
Section: Enzyme-based Eg-fetsmentioning
confidence: 99%
See 1 more Smart Citation
“…[60] To this extent, many nanomaterials, both carbon-based nanomaterials (e.g., multiwalled carbon nanotubes, [61][62][63] reduced graphene, etc.) and metal/metal oxide-based nanoparticles [64][65][66] have been used to develop external gate electrodes that exhibited a pH sensitivity by means of potentiometric measurements. [67][68][69] In this regard, Yin et al reported on the development of an H + ion-sensitive EG-FET by using an indium tin oxide (ITO) electrode modified with tin oxide (SnO 2 ) by a sputtering method.…”
Section: Enzyme-based Eg-fetsmentioning
confidence: 99%
“…[ 60 ] To this extent, many nanomaterials, both carbon‐based nanomaterials (e.g., multiwalled carbon nanotubes, [ 61–63 ] reduced graphene, etc.) and metal/metal oxide‐based nanoparticles [ 64–66 ] have been used to develop external gate electrodes that exhibited a pH sensitivity by means of potentiometric measurements. [ 67–69 ] In this regard, Yin et al.…”
Section: Enzyme‐based Eg‐fetsmentioning
confidence: 99%